PELUANG DAN TANTANGAN DIGITALISASI PENGAJARAN BAHASA ARAB DI MAN 4 MALUKU TENGAH - Mufidah, Nuril; Fitriani, Ismatul Hidayah; Bin Tahir, Saidna Zulfiqar (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to determine the opportunities and challenges of digitizing Arabic teaching at MAN 4 Central Maluku. This type of research is a descriptive case study by observing the teacher's teaching methods to students regarding Arabic learning, by utilizing digitalization as a means of supporting the success of students in understanding the material and introducing various digital learning media to students. The data collection process was carried out in three stages, namely observation, interviews, and documentation. The object under study is the teacher's teaching method to students, , by conducting interviews with one of the teachers and one of the students in MAN 4 Central Maluku as the subject under study. The documentation produced is a variety of digital learning media that are implemented for Arabic learning activities at MAN 4 Central Maluku. As a result, educators use various kinds of online applications such as Kahoot, Youtube, Google Form, Edmodo, Power Point, Google Site, Quizziz, Tiktok as a forms of digital implementation of Arabic language teaching at MAN 4 Central Maluku. This greatly affects the tenacity of teachers in facing the challenges of the times and packaging the material. Meanwhile for students, the effect of digitalization in Arabic learning activities has a positive impact because it can increase interest in learning, have curiosity, drive away boredom, and most importantly affect the quality of students' understanding.